Improving Students' Reading Comprehension Through The Know, Want, Learn (KWL) Technique - Tiwery, Dian Sartin (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2025)
The purpose of this research is to improve students' reading comprehension in narrative texts through the know want learn technique. The research method used qualitative with the type of classroom action research. This research used two cycles and each cycle consists of four steps, namely planning, action, observation, and reflection. There was a significant increase in their reading comprehension with KKM 70, namely: cycle (1) 65%, cycle (2) 100%. The increase in their reading comprehension was due to activities that can attract interest in the learning process. The KWL technique was designed to give students time to think in understanding the contents of a text. This activity makes students more confident in expressing their opinions. The conclusion of this research is that the KWL technique can improve students' reading comprehension